EFFECTIVENESS OF STUDENT WORKSHEET TO TRAIN OCEANIC LITERACY FOR JUNIOR HIGH SCHOOL STUDENTS - Millah Khoirul Mu'azzah; Siti Nurul Hidayati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
Nowadays literacy skills have become a necessary, therefore people of science must have scientific literacy skills which include oceanic literacy. Paciran area as an area close to the coast has low oceanic literacy skills. The aim of this study is to describe the effectiveness of student worksheet to train oceanic literacy for junior high school students. The focus of student worksheet contains only on oceanic literacy that has 3 aspects (content, process, and context). Design in this research is one group pretest-posttest design with 30 students in class VII-A SMPN 1 Paciran. The results of the effectiveness of student worksheets can be seen from the achievements oceanic literacy skills of students has increased with an N-Gain score of 0.83 with a high category. Out of  total 30 students, as many as 24 students received n-gain scores in the high category and 6 students received n-gain scores in the medium category. Increased students' oceanic literacy skills on the aspect of content obtained an N-Gain score of 0.69 in the medium category, the process aspect of 0.83 with a high category, and the context aspect of 0.91 with a high category. In this study, it can be concluded that student worksheet developed effectively used to train oceanic literacy for junior high school students declare eligible in terms of effectiveness based on the oceanic literacy test data, each student has a high category and the improvement oceanic literacy aspect data that has a high category. Keywords: Effectiveness of Student Worksheet, Oceanic Literacy, Interaction of  Living Thing.